1999
DOI: 10.1002/(sici)1097-0142(19990801)86:3<492::aid-cncr18>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The detection of renal carcinoma cells in the peripheral blood with an enhanced reverse transcriptase-polymerase chain reaction assay for MN/CA9

Abstract: BACKGROUND Using a reverse transcriptase–polymerase chain reaction (RT‐PCR) assay, the authors previously determined the expression of MN/CA9 mRNA in renal cell carcinoma (RCC) and its absence in benign renal tissue. In the current study, the utility of an enhanced RT‐PCR assay in the detection of renal carcinoma cells in the peripheral blood was assessed. METHODS An enhanced MN/CA9 RT‐PCR assay was applied to peripheral blood samples from a total of 96 patients. Forty‐two patients had renal tumors, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 17 publications
0
25
0
2
Order By: Relevance
“…Bluemke and colleagues screened the status of CTCs in the blood samples from renal carcinoma patients and revealed that the presence of CTCs correlated with the lymph node status and synchronous metastasis (9). The ability to detect CTCs by analyzing the expression of CA9 as a tumor-specific biomarker in blood samples has previously been reported (10)(11)(12)(13). RT-PCR for CA9 is a highly specific and sensitive technique for detecting CTCs shed from renal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bluemke and colleagues screened the status of CTCs in the blood samples from renal carcinoma patients and revealed that the presence of CTCs correlated with the lymph node status and synchronous metastasis (9). The ability to detect CTCs by analyzing the expression of CA9 as a tumor-specific biomarker in blood samples has previously been reported (10)(11)(12)(13). RT-PCR for CA9 is a highly specific and sensitive technique for detecting CTCs shed from renal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…McKiernan et al assessed CA9-expressing cells in 49% of a total of 37 RCC patients. Using the primers designated against exons 1 and 5, they detected the two variants of CA9 mRNA and, therefore, they did not reveal any correlation between CA9 expression and age, gender or tumor grade (10). The same set of primers with contrasting results was used in a further two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, CA II and CA IV have been identified in the mammalian kidney and implicated in the acidification of the excreted tubule fluid (22). Two more recently characterized transmembrane isoenzymes, CA IX and CA XII, are overexpressed in renal cell carcinomas and down-regulated by the product of the von Hippel-Lindau tumor suppressor gene (11,12,23,24). Based on immunocytochemistry and Western blotting of renal cancer cells, we can conclude that the effect of acetazolamide on invasion capacity is most likely attributable to inhibition of CA II and͞or CA XII.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36] To our knowledge, only 1 report has described the detection of disseminating tumor cells in RCC patients by applying RT-PCR for MN/CA9 mRNA. 20 After examining blood samples, they found circulating tumor cells in 49% of localized and in 59% of metastatic RCC patients. All positive samples originated from patients with RCC of the clear-cell type; in contrast, tumor-specific MN/CA9 mRNA could not be found in any of the patients with benign renal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…4 -7 Immunomagnetic cell-enrichment experiments could detect disseminated tumor cells for breast carcinoma, 8 -13 colon carcinoma, 14 -16 ovarian carcinoma, 12 head-and-neck squamous-cell carcinoma 17 and melanoma. 18 For renal-cell carcinoma (RCC), the dissemination of tumor cells in the bone marrow 19 and the detection of tumor-associated MN/CA9 mRNA in blood 20 have been reported.…”
mentioning
confidence: 99%